Reduction of potential radiological risks for patients undergoing diagnostic exams through modification of the X-ray spectrum - Gonzales-Ccoscco, Alberto E. (2024)
The diagnostic medical practice using X-rays significantly contributes to the collective dose worldwide, where the inherent risk in each examination is proportional to the absorbed dose, which is related to deterministic and stochastic effects of ionizing radiation. Therefore, due to the necessity of optimizing each radiological procedure, this study aimed to reduce the absorbed dose in patients undergoing X-ray examinations by evaluating each parameter that modifies the spectral distribution. The Birch and Marshall method was employed to reconstruct and modify the X-ray spectra based on tube voltage, filtration, tube current, anode angle, and energy pass factor. By modifying these parameters, it was possible to reduce the absorbed dose in the patient’s skin by up to 38%. The proposed methodology is feasible for implementation in clinical centers, given the availability of copper filters incorporated into X-ray equipment. Additionally, an alternative technique involving tantalum filters is presented, achieving a reduction in absorbed dose of up to 57%. Thus, with the developed methodology, it is demonstrated that it is possible to reduce radiation doses by modifying spectral distributions, reproducing medical images with a significant reduction in the absorbed dose on the patient, while ensuring quality and safety in X-ray diagnostic procedures.